2021
DOI: 10.1108/lthe-09-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

The use of technology in informal English language learning: evidence from Yemeni undergraduate students

Abstract: Purpose This study aims to explore the use of technology-based strategies by Yemeni undergraduate students to develop their English as a foreign language skills in informal learning settings. Design/methodology/approach A mixed methods research design was used to collect quantitative and qualitative data from 110 undergraduate students enrolled at the English Departments in two universities in Yemen. In the first phase of the study, 10 students were interviewed to obtain information about their use of techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 16 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…La Hanisi et al (2018) showed that students used WhatsApp in their formal learning which positively impacted their attitudes because of its ease of use and interest for the students. Bin-Hady and Al-Tamimi (2021) found that social media platforms positively impacted the perceptions of Yemeni EFL learners and can be used in informal learning settings.…”
Section: Discussionmentioning
confidence: 98%
“…La Hanisi et al (2018) showed that students used WhatsApp in their formal learning which positively impacted their attitudes because of its ease of use and interest for the students. Bin-Hady and Al-Tamimi (2021) found that social media platforms positively impacted the perceptions of Yemeni EFL learners and can be used in informal learning settings.…”
Section: Discussionmentioning
confidence: 98%
“…This fact cannot be stressed enough. The use of social networking sites by students in their second cycle of education is currently at an all-time high in terms of popularity (Alghamdi et al, 2021;Allam & Elyas, 2016;Alshabeb & Almaqrn, 2018;Bin-Hady & Al-Tamimi, 2021;Haque & Al Salem, 2019;Sharma, 2019;Slim & Hafedh, 2019). It teaches modern learners how to connect with peers not just in college but also off-campus, such as in the surrounding community.…”
Section: Social Mediamentioning
confidence: 99%
“…Social media networking is the technique of communication that is most often employed and used by people irrespective of their backgrounds in the contemporary world. Many studies have clearly established that students have a positive attitude toward social media use in education (Alghamdi et al, 2021;Bin-Hady & Al-Tamimi, 2021). In addition, several online networking platforms such as Flickr, Google+, Snapchat, YouTube, Tumblr Facebook, Facebook, Twitter, and Twitter, have added to a new dimension to educational technology expanding the horizons of online networking sites (Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social media also makes conversations and interactions possible between two or more people. Social networking sites like Google, Twitter, YouTube, Facebook, and LinkedIn hold a great deal of promise to help students learn online by helping them access information they can use to enrich, develop, edit, and sharpen their knowledge (Bin-Hady & Al-Tamimi, 2021;Gaytan, 2013). With the rapid development of technology and the meteoric popularity of social media, there are diverse opportunities today to evaluate learning and inspire learners (Bin-Hady et al, 2020;Gikas & Grant, 2013).…”
Section: Introductionmentioning
confidence: 99%